Correlation of Bullying Behaviour Experienced with the Mental Health of High School Students in Tomohon City - Dina Mariana Siregar (Universitas Muhammadiyah Banjarmasin, 2023)
This study aimed to determine the impact of bullying behavior on the mental health of high school students in Tomohon City. The results of this study show that bullying has an impact on the mental health of high school students in Tomohon City, as shown by the results of research conducted from May 1, 2023 to May 30, 2023 over 40 high school students in Tomohon City. Data collection was performed by assigning harassment impact scale via a Google Form to subjects who met the criteria. The results of multiple regression analysis obtained F = 17,189 (p < 0,001), and the results of the Pearson correlation test show that the significance value (p < 0,001), so it can be concluded that variables X and Y are correlated with each other. The Pearson correlation value of variables X and Y is -0,558. These results indicate that there is a negative relationship between bullying and mental health of high school students in Tomohon City. Based on these results, the hypothesis that the effects of bullying are negatively correlated with the mental health of high school students in Tomohon City is accepted. After performing the simple regression analysis test, an R-squared of 0.311 (p < 0,001). This means that after partial testing, bullying affected 31,1% of students' mental health and 68,9% were influenced by other factors not considered in the study.